Fungal endophytes in the tropical grasses Brachiaria brizantha cv. Marandu and B. humidicola - Rodrigues, Katia Ferreira; Filho, Moacyr B. Dias (Pesquisa Agropecuaria Brasileira, 1996)
A preliminary survey of fungal endophytes was conducted with species of Brachiaria cultivated at two active pastures in the State of Pari in the Brazilian Amazonia. Endophytic species, mostly fungi imperfecti, were isolated from leaves of Brachiaria brizantha cv. Marandu and B. humidicola. However, Acremoniumlike (clavicipitaceous endophytic anamorph) was isolated only from the leaf sheaths of B. brizantha cv. Marandu.